Analisis Perumusan Strategi Bisnis pada PT Samudera Nusantara Logistindo - Kuncoro, Engkos Achmad (Binus Business Review, 2010)
PT Samudra Nusantara Logistindo (PT SNL) is a company engaged in international cargo transportation services (international freight forwarder). Purpose of this study is to analyze the internal and external conditions and formulating business strategy and in order to gain competitive advantage for companies. The research method used in this research is a qualitative descriptive method research types such as of case studies. We have used Data Collection Techniques using interviews, surveys and questionnaires provided by the relevant parties in the company. These obtained data has been analyzed using a matrix IFE, EFE, CPM, TOWS, IE, SPACE, Grand Strategy and QSPM. The results of the IFE Matrix 2.885 and EFE Matrix are 2.623. The Result of the following Matrixes TOWS, SPACE, IE, Grand Strategy alternatives that can be applied in the company will be market penetration and product development strategy. The final results of this study concluded that the recommendation or proposal of an appropriate business strategy for the company based on the results obtained through a matrix of data processing is QSPM Market development strategy are then followed by the product development.Â